Management And Reporting Of Wakaf Assets Based On Psak Number 112 (Study Case At The Sulsel Ministry Of Religion) - Muhammad Ikram; Muryani Arsal.; Sahrullah, Sahrullah (International Journal of Economic Research and Financial Accounting, 2024)
The aim of this research is to find out how Waqf Assets are managed and reported based on PSAK Number 112 (Case Study at the Ministry of Religion of South Sulawesi). Apart from that, this research also wants to see how accountable waqf management is in the Ministry of Religion of South Sulawesi Province from a sharia enterprise theory perspective. This research is a type of qualitative research with a phenomenological study approach carried out using in-depth interview techniques with predetermined sources. The interview data that has been collected is reduced and then analyzed to draw a final conclusion. In order to maintain the quality of research results, a data validity test was carried out using data source triangulation. The results of the research reveal that the waqf accounting treatment at the South Sulawesi Provincial Ministry of Religion is still carried out simply and refers to the regulations issued by the central Ministry of Religion. The accounting treatment of waqf at the Ministry of Religion of South Sulawesi Province is specifically not in accordance with PSAK 112 which is due to the lack of adjustments in terms of standardization of accounting treatment carried out. Furthermore, from the sharia enterprise theory perspective, waqf management carried out by the Ministry of Religion of South Sulawesi Province has fulfilled the aspects of accountability and transparency as evidenced by the openness of information and the accountability model which is explained very clearly.